The material culture of the night school of Minas Gerais in the first decades of the Republic - Vera Lúcia Nogueira (Universidade Federal de Rondônia, 2018)
This paper analyzes the presence of material culture in the night primary school from the accounts of school subjects, teachers, principals and inspectors, as well as the modernization project of Minas Gerais education in which the materiality of the school is taken as a central concern pervading the discourses reformist political elite. The contemplated period refers to the initial two decades of the Republic. Through the theoretical and methodological references of The New Cultural History, the following sources were analyzed: reports of the directors and school inspectors, educational legislation and correspondence sent and received by the Secretary of the Interior. The organization of the night school destined to adult workers was inserted on the process of renewing education all across the country, by a group of reformations realized by a political elite that, taking the spot of idealist and builder of the Republic, invested in a project of school modernization characterized by material resources distribution, qualification of teaching practices and adequacy of school space. Ensuring the existence of the night school was one of the main government actions scoping the republic's reforms of primary public education at the beginning of the XX century in Minas Gerais.